How can the training of medical residents be improved? Three suggestions - Henna Vilppu; Mari Murtonen; Erika Österholm; Mirjamaija Mikkilä-Erdmann (Association for Medical Education in Europe (AMEE), 2022)
Background: The requirements for the quality of postgraduate medical education (PGME) have been increasing recently, due to changing demographics, patient service pressures and evolving healthcare systems. Furthermore, changes in medical knowledge and practice, and multiple challenges inherent in residents’ training make the development of PGME highly important.
Aim: To explore the experiences of internal medicine residents in PGME programme and suggest key features for future training.
Method: Twelve internal medicine residents were interviewed concerning their experiences with PGME. Data-driven analysis of the results was conducted, from which three themes regarding areas for development emerged.
Results: The most crucial areas to develop in PGME appeared to be: 1) utilisation of feedback and collegial support; 2) support for residents’ skills in coping with stress and developing emotion regulation strategies; and 3) fostering residents’ teaching skills and pedagogical practices in clinics.
Conclusions: The development of residents’ training should be supported with curriculum and carefully planned pedagogical solutions. In addition, training for teachers of residents should be improved.